The effect of HLA-DR on susceptibility to rheumatoid arthritis is influenced by the associated lymphotoxin alpha-tumor necrosis factor haplotype. - Newton, J; Brown, M; Milicic, A; Ackerman, H; Darke, C; Wilson, J; Wordsworth, B; Kwiatkowski, D (2003)
OBJECTIVE: HLA-DRB1, a major genetic determinant of susceptibility to rheumatoid arthritis (RA), is located within 1,000 kb of the gene encoding tumor necrosis factor (TNF). Because certain HLA-DRB1*04 subtypes increase susceptibility to RA, investigation of the role of the TNF gene is complicated by linkage disequilibrium (LD) between TNF and DRB1 alleles. By adequately controlling for this LD, we aimed to investigate the presence of additional major histocompatibility complex (MHC) susceptibility genes. METHODS: We identified 274 HLA-DRB1*04-positive cases of RA and 271 HLA-DRB1*04-positive population controls. Each subject was typed for 6 single-nucleotide polymorphisms within a 4.5-kb region encompassing TNF and lymphotoxin alpha (LTA). LTA-TNF haplotypes in these unrelated individuals were determined using a combination of family data and the PHASE software program. RESULTS: Significant differences in LTA-TNF haplotype frequencies were observed between different subtypes of HLA-DRB1*04. The LTA-TNF haplotypes observed were very restricted, with only 4 haplotypes constituting 81% of all haplotypes present. Among individuals carrying DRB1*0401, the LTA-TNF 2 haplotype was significantly underrepresented in cases compared with controls (odds ratio 0.5 [95% confidence interval 0.3-0.8], P = 0.007), while in those with DRB1*0404, the opposite effect was observed (P = 0.007). CONCLUSION: These findings suggest that the MHC contains genetic elements outside the LTA-TNF region that modify the effect of HLA-DRB1 on susceptibility to RA.